Loudness Perception Differentiation Using Repeating Sinus Rhythm - Mohamed Aminuddin, Mai Mariam; Mohd Nasir, Haslinah (Malaysia Technical Scientist Association (MALTESAS), 2017)

(untitled)
During the setting of hearing aid device process, the most comfortable loud (MLC) level is the most difficult level to determine with by existing methods i.e., verbal or behavioral technique. This is because the hearing aid device users should evaluate their own given the volume level. The users might find it confusing as this level is next to uncomfortable loud level (UC). UC level is not considered for the determination of the loudness scaling because in a long period it will damage the user’s hearing. The setting process will be more challenging if the user does not have any listening experience such as a child. Thus, the relationship in between the decline of the N100 wave peak and loudness perception is studied to distinguish between the MLC and UC for an objective loudness scaling measurement. As a result, the percentage decrease in N100 peak decreased with increasing volume is observed. From the results, it was found that for the level UC, the percentage decrease in peak N100 does not exceed 1.95% by 3 out of 7 subjects. While MLC showed the percentage decrease in N100 peak higher than UC and lower than the MEDIUM. In conclusion, the loudness perception can be measured by the percentage decrease in peak N100 and this method can be used to adjust the hearing aid device objectively.